Hairy cell leukemia with CCND1/IGH fusion gene and BRAF V600E mutation. (2020) - Rahman, Zaid Abdel; Muwalla, Firas; Jiang, Liuyan; Foran, James
Abstract: A 75-year-old male evaluated for pancytopenia. Abnormal lymphocytes with hairy projections noted on peripheral blood. Bone marrow examination showed diffuse proliferation of CD20+ B-lymphocytes. Flowcytometry revealed monoclonal lambda-restricted B-cells expressing CD19, CD20, CD11c, CD103, CD25 and CD123, negative for CD5 and CD10. Additional staining showed positivity for cyclin-D1, Annexin-A1 and TRAP. FISH identified t(11;14). PCR was positive for BRAF V600E. Given the above findings, nonspecificity of t(11;14) and the presence of BRAF V600E; the diagnosis of HCL was favored. Patient achieved CR with infusional cladribine. Herein, we report the co-occurrence of CCND1/IGH and BRAF V600E in HCL, a rare scenario that could characterize a new subtype of HCL.